An analytical comparison between point-of-care uric acid testing meters. (3rd March 2016) - Paraskos, Jonathan; Berke, Zsofia; Cook, Jason; Miner, Jeffrey N.; Braddock, Martin; Platt, Adam; Hughes, Glen
ABSTRACT: Objective : A key goal in gout treatment is achieving sustained serum uric acid (sUA) lowering. Point-of-care test (PoCT) meters provide convenient, rapid measures of sUA levels to monitor/adjust therapy. Four commercially available sUA PoCT meters were compared qualitatively (ease of use) and quantitatively (precision/accuracy). Methods : Liquid chromatography mass spectrometry (LC-MS) analysis was used as a laboratory reference method to compare precision of PoCT devices using blood samples from 20 healthy volunteers. Accuracy was compared against the LC-MS reference method and a laboratory clinical chemistry platform. Results : Qualitatively, EasyTouch ® GU and UA Sure were least user-friendly, requiring repeated attempts for accurate use. HumaSens and BeneCheck provided good usability and assay precision. Cross-validation of meter precision with laboratory-based uricase assay gave good correlations between both methods (R 2 = 0.8061 and 0.7605, respectively). Conclusion : UA PoCT meters can be important in managing gout, and the characteristics compared herein may enhance successful patient uptake.